Kajian Analisis Spasial Penentuan Tipe Iklim Menurut Klasifikasi Schmidt – Ferguson Menggunakan Metode Thiessen – Polygon di Provinsi Riau - Edi Rahmanto; Sabila Rahmabudhi; Tia Kustia (Buletin GAW Bariri, 2022)
The pattern diversity of climatic elements is very important in determining climate classification. There are various types of climate classification systems used in Indonesia, one of which is the Schmidt–Ferguson climate classification. The climate classification according to Schmidt–Ferguson is more suitable for use in the plantation sector, because it has advantages such as being suitable for tropical areas, paying close attention to temperature fluctuations, simple data analysis and suitable for the whole world. This study aims to identify climate types and map climate types spatially based on the Schmidt–Ferguson climate classification. The climate identification process is combined with a geographic information system (GIS), so that climate types can be displayed in the form of a spatial mapping based on climate type. The method used is the Thiessen Polygon method, then mapped spatially using Arcview software version 10.4.1. From the analysis and mapping, it was found that based on the Schmidt–Ferguson climate classification, Riau Province has 4 climate types, namely climate type B (wet), climate type A (very wet), climate type C (half wet), and climate type D (moderate). In general, Riau Province has a type B climate, which is included in an area with tropical rain forest vegetation with a wet climate, generally suitable for dense trees such as palm trees. This is in line with the condition of plantations in the Province, where most of the area is fertile and overgrown with oil palm plantations.